Perbedaan pH Saliva antara Remaja Wanita Pre Menarche dengan Remaja Wanita Post Menarche - Syamsudduha, .; AR, Risya Cilmiati; Subiyantoro, Pradipto (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Riskesdas (riset kesehatan dasar) in 2007 result that women get more curative treatment of tooth healt. One factor that influence tooth healt is pH saliva. This research aims to know the difference of salivary pH between young women of pre menarche with young women of post menarche.. Methods: This research was an observational research using cross sectional approach and had been done in UNS Medical Faculty, TPA al-falah, and TPA al-ikhlas. Data was collected by using purposive random sampling method devide into 2 group (1.) pre menarche group, (2.) post menarche group. The subjek of first group is student of medical faculty of 2008, 2009, and midwifery 2011 UNS and second group is pupil of TPA al-Ikhlas and TPA al-Falah recidency of Surakarta. Two of group which a fullfil of inklusion and exclusion criteria compare of the pH. The data analysis used compare means independent-samples T-test Â SPSS 20.0 for Windows. Results: this research shows (1) average salivary pH in pre menarche group is 6,867 dan post menarche group is 7,240. (2) results of compare means independent-samples T-test shows p = 0,00. Conclusions: This study found the difference of salivary pH between young women of pre menarche with young women of post menarche. Keywords: : salivary pH of pre menarche, salivary pH of post menarche, status of menstruation.